Brief report: Borderline personality symptoms and perceived caregiver criticism in adolescents. (16th April 2015) - Whalen, Diana J.; Malkin, Mallory L.; Freeman, Megan J.; Young, John; Gratz, Kim L.
ABSTRACT: Despite findings of an association between adolescent psychopathology and perceived parental criticism, the relation between adolescent borderline personality disorder (BPD) symptoms and perceived parental criticism has not been examined. Given the centrality of interpersonal sensitivity to BPD (relative to other forms of psychopathology), we hypothesized that adolescent BPD symptoms would be uniquely related to perceived caregiver criticism, above and beyond other forms of psychopathology and general emotion dysregulation. Adolescents ( N  = 109) in a residential psychiatric treatment facility completed self‐report measures of BPD symptoms, perceived caregiver criticism, emotion dysregulation, and symptoms of depression, anxiety, and posttraumatic stress disorder. Results revealed a unique relation of adolescent BPD symptoms to perceived caregiver criticism, above and beyond age, gender, and other forms of psychopathology. Findings suggest that adolescent BPD symptoms may have unique relevance for adolescents' perceptions of caregivers' attitudes and behaviors, increasing the likelihood of negative perceptions. Highlights: Borderline personality disorder (BPD) is associated with interpersonal sensitivity. Adolescents with BPD symptoms may be sensitive to criticism from caregivers. We examined the relation of adolescent BPD symptoms to perceived parental criticism. These relations were examined among adolescents in residential psychiatric treatment. BPD symptoms were uniquely related to perceived parental criticism.